PENGARUH KINERJA KARYAWAN TERHADAP KEPUASAN NASABAH PADA PT. PEGADAIAN (PERSERO) UPC PASAR SEGAR PAAL DUA MANADO - Veren Prang; Meiske Manopo; Lietje Lumatauw (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2022)
Employee performance has an important role for a company, especially service companies. Employee performance must be able to provide satisfaction to its customers. So this study aims to determine the effect of employee performance on customer satisfaction at PT. Pegadaian (Persero) UPC Pasar Segar Paal Dua Manado. The type of research is quantitative research and research methods using descriptive research methods, field research methods and literature review research methods. Research that takes a sample from one population by using a questionnaire as a data collection tool. The population taken is customers at PT. Pegadaian (Persero) UPC Pasar Segar Paal Dua Manado. The customers in question amounted to 80 people but the sample involved was 44 respondents using the Simple Random Sampling method. The analysis used is descriptive statistical analysis, total score, correlation analysis and simple linear regression analysis. The results of research analysis correlation coefficient value r = 0,756 (75.6%) indicate that employee performance has a strong and significant relationship to customer satisfaction at PT. Pegadaian (Persero) UPC Pasar Segar Paal Dua Manado. The coefficient of determination shows that 57.2% customer satisfaction is influenced by employee performance, while the remaining 42.8% is influenced by other factors. The results of the analysis show that employee performance has a significant influence on customer satisfaction at PT. Pegadaian (Persero) UPC Pasar Segar Paal Dua Manado. For this reason, employee performance needs to be considered by leaders and companies so that they can increase customer satisfaction.